Durability of Cross-Protection by Different Schedules of the Bivalent HPV Vaccine: The CVT Trial. (5th March 2020) - Tsang, Sabrina H; Sampson, Joshua N; Schussler, John; Porras, Carolina; Wagner, Sarah; Boland, Joseph; Cortes, Bernal; Lowy, Douglas R; Schiller, John T; Schiffman, Mark; Kemp, Troy J; Rodriguez, Ana Cecilia; et al.
Abstract: Background: The Costa Rica HPV Vaccine Trial has documented cross-protection of the bivalent HPV vaccine against HPV31/33/45 up to 7 years after vaccination, even with one dose of the vaccine. However, the durability of such protection remains unknown. Here, we evaluate the efficacy of different schedules of the vaccine against HPV31/33/45 out to 11 years postvaccination, expanding to other nontargeted HPV types. Methods: We compared the rates of HPV infection in vaccinated women with the rates in a comparable cohort of unvaccinated women. We estimated the average vaccine efficacy (VEavg ) against incident infections and tested for a change in VE over time. Results: Among 3-dose women, we observed statistically significant cross-protection against HPV31/33/45 (VEavg = 64.4%, 95% confidence interval [CI] = 57.7% to 70.0%). Additionally, we observed borderline, statistically significant cross-protection against HPV35 (VEavg = 23.2%, 95% CI = 0.3% to 40.8%) and HPV58 (VEavg = 21.2%, 95% CI = 4.2% to 35.3%). There was no decrease in VE over time (two-sided P trend > .05 for HPV31, -33, -35, -45, and -58). As a benchmark, VEavg against HPV16/18 was 82.0% (95% CI = 77.3% to 85.7%). Among 1-dose women, we observed comparable efficacy against HPV31/33/45 (VEavg = 54.4%, 95% CI = 21.0% to 73.7%). Acquisition of nonprotected HPV types was similar between vaccinated and unvaccinated women, indicating that the difference in HPV infection rates was not attributable to differential genital HPV exposure. Conclusions: Substantial cross-protection afforded by the bivalent vaccine against HPV31/33/45, and to a lesser extent, HPV35 and HPV58, was sustained and remained stable after 11 years postvaccination, reinforcing the notion that the bivalent vaccine is an effective option for protection against HPV-associated cancers.